Experimental and correlation study of selected physical properties of aqueous blends of potassium sarcosinate and 2-piperidineethanol as a solvent for CO2 capture - Garg, S. (Institution of Chemical Engineers, 2017)
In this work, physical properties such as density, refractive index, and viscosity of aqueous blends of potassium sarcosinate (K-Sar) and 2-piperidineethanol (2-PE) were measured at temperatures ranging from 298.15 to 333.15 K. Several concentrations of K-Sar and 2-PE blends were prepared in terms of mass fraction (0.04 + 0.16, 0.08 + 0.12, 0.12 + 0.08, 0.16 + 0.04, and 0.20 + 0), respectively. From the results, it was observed that all physical properties data decreases with the rise in temperature of the solution. While, density increases with increase in concentration of K-Sar in the aqueous blended solution, and refractive index and viscosity decrease with increase in K-Sar concentration in the solution. Both density and refractive data were correlated as a function of concentration and temperature using modified form of Graber's equation. However, a modified Vogel–Tamman–Fulcher equation was utilized for correlating the experimental viscosity data of aqueous blend. Experimental density data were used to calculate the coefficient of thermal expansion. It increases marginally with increase in concentration and temperature. Moreover, ANOVA analysis was performed for all the physical properties data. © 2016 Institution of Chemical Engineers